2006
DOI: 10.1016/j.molimm.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Complement-coated antibody-transfer (CCAT); serum IgA1 antibodies intercept and transport C4 and C3 fragments and preserve IgG1 deployment (PGD)

Abstract: In periodontal disease, IgG1 and IgA1 antibodies produced in situ deposit on antigens in the affected tissues. Thus, there is an interest in the effect of co-deposited IgA1 antibodies on complement activation by IgG1-immune complexes. In the present study, we first analyzed the effect of IgA1-immune complexes on complement using human IgA1 antibodies to dansyl (with dansylated human serum albumin serving as the immobilized antigen). It was observed that these IgA1-immune complexes when incubated for prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…By preventing complement-mediated membrane damage, CD59 conveys an immunological privilege to both normal host and neoplastic cells [ 1 , 5 , 6 , 32 ]. The soluble complement inhibitor, C1-inhibitor, acts at the sensitized surface to remove C1 and block the classical pathway, but a highly effective initiation of the classical complement pathway by abundant levels of complement-activating polyclonal antibodies to numerous proximate antigenic determinants on cancer cell surfaces may override C1-inhibitor [ 10 - 12 ], and, as shown here, may generate a profound fixation of complement that results in a significant percentage of cell killing as measured by the release of LDH and uptake of Trypan Blue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By preventing complement-mediated membrane damage, CD59 conveys an immunological privilege to both normal host and neoplastic cells [ 1 , 5 , 6 , 32 ]. The soluble complement inhibitor, C1-inhibitor, acts at the sensitized surface to remove C1 and block the classical pathway, but a highly effective initiation of the classical complement pathway by abundant levels of complement-activating polyclonal antibodies to numerous proximate antigenic determinants on cancer cell surfaces may override C1-inhibitor [ 10 - 12 ], and, as shown here, may generate a profound fixation of complement that results in a significant percentage of cell killing as measured by the release of LDH and uptake of Trypan Blue.…”
Section: Discussionmentioning
confidence: 99%
“…However in the absence of sufficient levels of antibody deposition, this and other complement control mechanisms tend to restrict the ability of complement to eliminate cancer cells [ 2 , 5 - 9 ]. Current therapeutic mAbs as well as endogenous low affinity IgG antibodies to cancer cells often recruit the complement component C1qr 2 s 2 with such low avidity that serum C1-inhibitor is able to rapidly inhibit activated C1r and C1s, and in most cases quickly remove the entire C1qr 2 s 2 complex from the antibody-coated cell surface, resulting in only a trace level of C4b-deposition [ 10 - 12 ]. Meanwhile, CD55 and CD46 on malignant cells restrict deposited C4b and C3b, and CD59 inhibits complement membrane attack complex formation, therein protecting cancer cells from membrane damage [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, other IgA effector functions are strongly modulated by the N- glycans at the tailpiece. First, N- glycosylation positively influences IgA1 binding to complement C3 – complement coated-IgA carries out the complement-coated antibody-transfer (CCAT) mechanism (19, 62). Second, absence of N- glycans at the tailpiece site induces the formation of IgA dimers (19).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the difference might also be attributed to the specificity of the anti-human IgA conjugate. More specifically, it has been demonstrated that IgA1 and IgA2 have different properties, with IgA2 exhibiting pro-inflammatory properties linked to glycosylation [ 31 , 32 , 33 ]. Further studies are needed to analyze the differences between Darrah et al’s results and our findings, in order to continue to understand the anti-PAD4 response and isotype usage and to further elucidate the utility of anti-PAD4 IgA as a biomarker in RA.…”
Section: Discussionmentioning
confidence: 99%